Fast response of cold ice-rich permafrost in northeast Siberia to a warming climate - Jan Nitzbon (Nature Portfolio, 2020)
Siberian Arctic permafrost contains vast stores of carbon, the fate of which is dependent on the climate. Here the authors use models of future scenarios to show that under the direst climate changes up to 2/3 of the stored organic carbon could thaw.